Optimization of Working Temperature and Determination of Dross Recycle Soldering Machine Control Type Based on Specific Energy Consumption - Farhan, Ridho Muhamad; Wibowo, Ignatius Agung (Universitas Mercu Buana, 2025)
Solder Dross Recycle (SDR) machine role is to extract solder out of solder dross. SDR machine has two parameters which are working temperature and controller type. There are three working temperature references which are 220 °C, 250 °C, dan 298 °C. Controller type of the machine are available for two options which are ON-OFF and PID controller. The aim of this research is to determine working temperature combination and controller type. The SDR machine is tested with variations of working temperature and controller type. Data needed for choosing the best working temperature are extracted solder mass (ESM) and energy consumption (EC). EC is obtained from measurement by digital power meter, while MST is obtained by measuring final solder weight. EC is divided by MST to obtain Specific Energy Consumption (SEC). Data needed for choosing the best controller type is electrical power which is recorded every 10 minutes. Testing period is decided to be 200 minutes. The result of working temperature testing showed that the bigger the working temperature the smaller the KES so that the suitable working temperature in this experiment is 298 °C. The result of controller type testing showed that the smallest SEC was in PID controller with the working temperature of 298 °C which is 0.55 kWh/kg. The SEC value of 0.55 kWh/kg is less as much as 10.9% than the smallest SEC value of ON- OFF controller whose working temperature is 298 °C which is 0.61 kWh/kg. The chosen working temperature based on SEC is 298 °C with SEC of 0.55 kWh/kg out of 220 °C and 250 °C. The chosen controller type is PID controller with SEC of 0.55 kWh/kg with setting of Kp. Ki, and Kd respectively are 9, 250, and 7 out of ON-OFF controller with hysteresis setting of 0.5 °C.